Decreasing the rate of motorcycle accidents in Malaysia: analytical hierarchy process approach - Mokhtar, Nur Hazwani; Hamzah, Luqman Hakim; Che Mamat, Husni; Mohammad Nasir, Mohd Zakaria; Mamat, Mohd Fauzi (2023)
The highest proportion of road traffic deaths in Southeast Asia is primarily due to motorcycle accidents at a rate of 34%. The prevalence of motorcycle accidents remains a significant challenge in Malaysia. Nevertheless, the motorcycle is still the most popular mode of transport across Southeast Asian countries for various purposes, including courier service, fast food delivery, and commuting to work. Some factors that have been identified to decrease the rate of motorcycle accidents are motorcycle safety technology, efficient law enforcement, car safety technologies, awareness through education, and cutting-edge infrastructure. Past studies have only focused on those elements without integrating the perceptions of vehicle drivers and motorcyclists on factors that can reduce the escalating rate of motorcycle accidents. As such, this study captured the perceptions of Malaysian drivers on the effectiveness of several methods to minimise the rate of fatalities among motorcyclists. The main focus here refers to motorcycle safety technology, law enforcement, car safety technology, education, and infrastructure. A hierarchy framework that prioritises customer requirements is proposed in this study based on perceptions of vehicle drivers and motorcyclists on reducing the rate of motorcycle accidents in Malaysia via Analytical Hierarchy Process (AHP) approach. As a result, motorcycle and car safety technologies emerged as the top priority amongst motorcyclists and vehicle drivers, respectively, to decrease the rate of motorcycle accidents